Enduring neurobehavioral effects of early life trauma mediated through learning and corticosterone suppression - Moriceau, Stephanie; Raineki, Charlis; Holman, Jennifer D.; Holman, Jason G.; Sullivan, Regina M. (Frontiers in Behavioral Neuroscience, 2009)
Early life trauma alters later life emotions, including fear. To better understand mediating mechanisms, we subjected pups to either predictable or unpredictable trauma, in the form of paired or unpaired odor-0.5mA shock conditioning which, during a sensitive period, produces an odor preference and no learning respectively. Fear conditioning and its neural correlates were then assessed after the sensitive period at postnatal day (PN)13 or in adulthood, ages when amygdala-dependent fear occurs. Our results revealed that paired odor-shock conditioning starting during the sensitive period (PN8-12) blocked fear conditioning in older infants (PN13) and pups continued to express olfactory bulb-dependent odor preference learning. This PN13 fear learning inhibition was also associated with suppression of shock-induced corticosterone, although the age appropriate amygdala-dependent fear learning was reinstated with systemic corticosterone (3mg/kg) during conditioning. On the other hand, sensitive period odor-shock conditioning did not prevent adult fear conditioning, although freezing, amygdala and hippocampal 2-DG uptake and corticosterone levels were attenuated compared to adult conditioning without infant conditioning. Normal levels of freezing, amygdala and hippocampal 2-DG uptake were induced with systemic corticosterone (5mg/kg) during adult conditioning. These results suggest that the contingency of early life trauma mediates at least some effects of early life stress through learning and suppression of corticosterone levels. However, developmental differences between infants and adults are expressed with PN13 infants’ learning consistent with the original learned preference, while adult conditioning overrides the original learned preference with attenuated amygdala-dependent fear learning.